2002
DOI: 10.1183/09031936.02.00742002
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac diastolic function and hypercapnic ventilatory responses in central sleep apnoea

Abstract: Hyperventilation is the key factor contributing to the development of idiopathic nonhypercapnic central sleep apnoea (ICSA), where left ventricular systolic function is normal. ICSA is reported to occur in 20% of patients with left ventricular diastolic dysfunction, in whom elevated pulmonary vascular pressures and resultant increased pulmonary vagal afferent traffic may contribute to hyperventilation. The contribution of the two potential mechanisms responsible for the hyperventilation seen in the following I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 31 publications
(58 reference statements)
0
7
0
Order By: Relevance
“…The normalisation of respiration and elimination of central apnoeas by ASV in contrast to CPAP therapy supports observations that hyperventilation plays an important role in the pathophysiology of both CSR-CSA and CSA [3,4,20,35]. Hall et al [36] described only gradual differences between these two conditions.…”
Section: Discussionmentioning
confidence: 77%
“…The normalisation of respiration and elimination of central apnoeas by ASV in contrast to CPAP therapy supports observations that hyperventilation plays an important role in the pathophysiology of both CSR-CSA and CSA [3,4,20,35]. Hall et al [36] described only gradual differences between these two conditions.…”
Section: Discussionmentioning
confidence: 77%
“…Insomnia and daytime sleepiness are common symptoms. Elevated hypercapnic ventilatory responses (64, 70, 71) leading to increased propensity for hypocapnia and respiratory control instability are believed to be particularly important pathophysiolgical traits in ICSA. While arousal may play an important role in terminating hypopnea/apneas in patients with ICSA, the subsequent hypocapnia that develops appears to play an important role in further destabilization of breathing (60).…”
Section: Mechanisms Of Central Sleep Apneamentioning
confidence: 99%
“…Solin et al [32] showed that hypercapnic ventilatory responses in patients with idiopathic central sleep apnoea were the same in patients with and without diastolic dysfunction. Mansfield et al [33] reported that a successful heart transplantation led to a switch from CSA-CSR to (I)CSA.…”
Section: Csa-pattern and Ventilation Parametersmentioning
confidence: 99%